Seroprevalence of Toxoplasma gondii Infection in Wild Boar (Sus scrofa) and Korean Water Deer (Hydropotes inermis argyropus) in the Republic of Korea - Jusun Hwang; Jisoo Kim; Kidong Son; Yongkwan Kim; Hyesung Jeong; Weonhwa Jheong (Animals)
Toxoplasma gondii is a ubiquitous zoonotic parasite with a wide range of warm-blooded animals as intermediate hosts, where the transmission primarily occurs through ingesting T. gondii oocysts in the environment. Hence, animals inhabiting a wide geographical range can be sentinels for the environmental contamination of T. gondii oocysts. The aim of this study was to determine the seroprevalence of T. gondii in two generalist ungulates in the Republic of Korea (ROK), wild boar (Sus scrofa) and Korean water deer (Hydropotes inermis argyropus), and identify the risk factors associated with this infection. Commercial ELISA kits confirmed a seroprevalence of 34.9% in wild boar (170/487, 95% CI: 30.7–39.3%) and 29.9% in Korean water deer (135/452, 95% CI: 25.7–34.3%). In both species, the seroprevalence was highest in winter, and showed no sex-related differences. In wild boars, the seroprevalence showed steep reduction in 2020 and increased with body mass. Meanwhile, in Korean water deer, seroprevalence did not show significant association with any of the tested variables, although an increase in seroprevalence was observed in 2020 compared to previous years. This study documents the widespread yet heterogeneous nature of T. gondii prevalence in its intermediate host population. Hence, the constant monitoring of T. gondii prevalence in its host species, both definitive and intermediate, while simultaneously considering risk factors would be necessary to identify the drivers behind the fluctuating pattern of T. gondii prevalence.